Kant: la loi et ses ricochets - Zupančič Žerdin, Alenka (Filozofski vestnik, 1995)
The paper deals with numerous paradoxes of the Kantian postulates of the immortality of the soul in relation to the moral law
Keywords: ethics; etika; filozofija; Kant, Immanuel; nemška filozofija; philosophy; postulati; študije in kritike